2017
DOI: 10.12968/ijpn.2017.23.11.558
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nurses towards care of the dying patient in India

Abstract: Conferences and low-fidelity simulation are effective methods for improving nurses' knowledge of end-of-life care in India. Improved education surrounding end of life may positively affect attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
11
2
1
Order By: Relevance
“…This study showed that the overall attitudes toward hospice care score, median 102.00(interquartile range, 95.5-120.50), among front-line nurses was higher than that found in studies by Karadag 21 but lower than that found in the study by Ho et al (Mean + SD, 116.8 + 11.4). 22 Therefore, the nurses' attitudes toward hospice care was moderate.…”
Section: Discussioncontrasting
confidence: 65%
“…This study showed that the overall attitudes toward hospice care score, median 102.00(interquartile range, 95.5-120.50), among front-line nurses was higher than that found in studies by Karadag 21 but lower than that found in the study by Ho et al (Mean + SD, 116.8 + 11.4). 22 Therefore, the nurses' attitudes toward hospice care was moderate.…”
Section: Discussioncontrasting
confidence: 65%
“…The attitudes towards death among participants in our study were more positive than those found among nursing students in Palestine and Turkey, 15 28 similar to those found among nursing students in the USA 29 and poorer than those found among nursing students in Sweden. 30 Further, our sample of nursing students had more positive attitudes than those found among registered nurses in China, 8 India, 31 32 Ethiopia, 33 Saudi Arabia 17 and Japan 9 ; however, nurses in Israel 5 and the USA 34 have been found to have more positive attitudes than those seen in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…33 Conversely, older nurses (especially those 50 years and older) and those with a higher number of years of experience, were found to be the strongest indicators of exhibiting a positive attitude toward caring for dying patients. 13,23,33,34 Therefore, in order to ensure that sociodemographic comparisons (i.e., age, gender and years of experience comparisons) are valid and accurate, the items of the FATCOD-SF must have equivalent meaning across these subgroups. 35,36 To our knowledge, no previous studies have investigated the influence of gender, age and experience on the FATCOD items.…”
Section: Discussionmentioning
confidence: 92%